Semicrystalline Shape‐Memory Elastomers: Effects of Molecular Weight, Architecture, and Thermomechanical Path. Issue 12 (14th November 2017) - Lee, Hojun; Yang, Jeh‐Chang; Thoppey, Nagarajan; Anthamatten, Mitchell
Abstract: Poly(caprolactone) networks are well‐studied shape‐memory polymers owing to their high fixity and recovery, their ability to store large amounts of elastic energy, and their tunable shape‐triggering temperature. To elucidate the influence of network structure on shape‐memory features, poly(caprolactone) networks are prepared by reacting different molecular weight diacrylate prepolymers with trifunctional (trimethylolpropane tris(3‐mercaptopropionate), 3T ) or tetrafunctional (pentaerythritol tetrakis(3‐mercaptopropionate), 4T ) crosslinkers. Networks from4T crosslinkers generally exhibit higher gel fractions, more elastically active strands, and superior shape‐memory properties compared with networks from3T . Melted elastomers exhibit stress–strain behavior well described by the neo‐Hookean model. How the state of crystallization during the cold‐drawing process has a large effect on the draw stress, the network's shape fixity, and its elastic storage capacity is shown. Finally, the working strain range of networks is evaluated. Cured elastomers prepared from prepolymers with different molecular weights can store and release large amounts of elastic energy (>2 MJ m −3 ), over different ranges of tensile strain. Abstract : The effect of architecture and molecular weight on shape‐memory performance is examined for a series of poly(caprolactone) networks prepared using thiol–ene click chemistry. A sample's thermomechanical history, especially cold drawing, is shown to have a significant impact on shape‐memory fixity and the amount of recoverable elastic energy.